Mobilization of Language as an Indicator of Ethnic Identity in the Social Practices of Kazakhs in Mongolia - Guldaria Iskakova, Nazgul Baigabatova, Amangeldy Tolamissov, Saira Rakhipova,; Myrzatayeva, Zabira (Opción, 2019)
The purpose of the article is to identify the role of the Kazakh language in the processes of ethnic external identification and internal self-identification via cognitive anthropology as the method that included observation, semi-structured interviews, and case studies. As a result of theoretical and empirical research, it was revealed that the role of the Kazakh language in the formation of the ethnic identity of the diaspora remains an important indicator of ethnic identity. In conclusion, Kazakh language for representatives of diaspora remains an important indicator of ethnic consciousness